Ability of Non-Medical Female Employees Towards Self Breast Assessment - Desai, Purnima M.; Gholap, Manisha C. Gholap; Shinde, Mahadeo B; Choudhari, Samir K. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The breast cancer is commonly found among women in developing countries. Early detection plays a very important role in breast cancer,the Breast self-examination is simple, non-invasive and inexpensive method. Objectives: (1) To assess the existing knowledge regarding self breast examination among non-medical female employees.(2) To assess the capacity to do self breast examination among non-medical female employees. (3) To find the association between existing knowledge score with selected socio demographic variables. Methods:Evaluative research approach, The participants consists of 49 non medical female employees were selected through purposivesampling technique. The data were collected by structured questionnaire. The data analyzed using spss software. Results: The pre-testmean knowledge score was 4.551 and post-test mean score was 17.265.The t-test value was 61.053 and was found significant at p